O licenciamento ambiental como instrumento de efetivação do direito ao meio ambiente ecologicamente equilibrado na perspectiva de um desenvolvimento sustentável - Teixeira, Leopoldo Fontenele (2013)
Humanity, nowadays, live in a context of risk society, characterized by the existence of unseen risks, of great magnitude, being the result of exponential scientific and technological development by which it has experienced throughout its history. These risks can not be eliminated, but can be managed, which requires an active attitude of both state and society. The law responds to these demands of post-modernity, turning into a preventive and functional character. The state is restructured based on paradigm called Social and Environmental State of Law, which brings to the limelight of state duties environmental issues, although not disengage from the task of achieving the fundamental social right effectiveness. This state model is based on the principle of solidarity and the recognition of the fundamental right to a healthy environment to future generations. The environment is elevated to a fundamental right of the third dimension. It is rehabilitated fundamental duties as an independent category from fundamental rights. The Constitution of 1988 is an example of ecological constitution. This Charter contains the right to live in a healthy and balanced environment as a fundamental right and duty, taking the enviroment in a macro context, marked by diffuse and intergenerational ownership and essential to a healthy and dignified life. In this context, the paper deals about the administrative process of environmental licensing as a mean of enforcement of this right and duty. Study its concept, essence, its relationship with the environmental principles of precaution, prevention and polluter pays, its procedure and its relation to the principle of sustainable development. Addresses the environmental license, its concept, essence, species, cases of modification, suspension and termination. Discusses the corrective licensing, as well as the risk of self-licensing, suggesting the adoption of the model environmental regulatory agencies as a technique to overcome this problem. The methodology is bibliographical, theoretical, descriptive, exploratory and dialectical predominantly inductive. It is concluded that the environmental licensing is one of the most important instruments for ensuring the fundamental right to an ecologically balanced environment, seen from the perspective of sustainable development.